GOVERNANCE AND FINANCIAL PERFORMANCE EFFECTS: MODERATING ROLE OF FIRM SIZE - Marina, Yesi; Muhyarsyah, Muhyarsyah (Jurnal Akuntansi, Keuangan, Pajak dan Informasi (JAKPI), 2026)
This study examines the influence of financial performance, audit committee effectiveness, and institutional ownership on firm value, with firm size acting as a moderating variable, in mining companies listed on the Indonesia Stock Exchange during 2022–2024. This period reflects the post-commodity price peak normalization phase, characterized by heightened market volatility and increasing pressure on corporate valuations. Financial performance is proxied by Net Profit Margin (NPM), audit committee effectiveness by the frequency of audit committee meetings, institutional ownership by the proportion of institutional shareholdings, and firm value by Price to Book Value (PBV). Using a quantitative research design, this study analyzes balanced panel data from 54 mining firms, resulting in 162 firm-year observations, and applies Moderated Regression Analysis (MRA) using EViews 12. The findings indicate that NPM and audit committee effectiveness have a significant positive effect on PBV, suggesting that profitability and active oversight enhance market valuation, while institutional ownership does not significantly affect firm value. Furthermore, firm size weakens the relationship between NPM and PBV, implying that the marginal impact of profitability on valuation declines as firms grow larger; however, firm size does not moderate the effects of audit committee effectiveness and institutional ownership. These results support Stewardship Theory and provide practical implications for corporate management and institutional investors in optimizing governance and financial strategies under post-boom commodity market conditions.